Prove that $a^3-b^3 = 2011$ has no integer solutions.

I think the question is wrong as

$a^3-b^3 = 2011$

$(a-b)(a^2+ab+b^2) = 2011$

As $2011$ is prime so the only factors $2011$ has are $1$ and $2011$ itself.

So if $a-b = 1$ and $a^2+ab+b^2 = 2011$ , then we can say that

$a^2-2ab+b^2 = 1$

So , $a^2+b^2 = 2ab+1$

Putting the value in the second equation

$3ab +1 = 2011$

$3ab = 2010$

And as $2010$ is divisible by $3$ it has integer solutions , which is contradictory to the original question. Can anybody help me with this?

  • 1
    $\begingroup$ Questions are made by human beings, so they are wrong sometimes. What values of $a$ and $b$ did you find? Did you check they satisfy $a^3-b^3=2011$? Note that you are looking for factors $a$ and $b$ of $2010/3=670$ such that $a-b=1$. Do such numbers exist? $\endgroup$
    – Taladris
    May 24 at 10:53
  • 1
    $\begingroup$ $25 \times 26 < 670 < 26 \times 27.$ $\endgroup$ May 24 at 10:56
  • 2
    $\begingroup$ You need to verify that the divisors of $ab=670$ with $a-b=1$ really satisfy $a^3-b^3=2011$. So far there is no contradiction to the original question as you claim. $\endgroup$ May 24 at 10:57
  • $\begingroup$ @user2661923 Exactly, this is what I said. Everything lines up with the original question. There is no mistake as claimed. Indeed, there really are no solutions. $\endgroup$ May 24 at 10:59
  • 5
    $\begingroup$ Yes, $3ab = 2010$ has integer solutions, but remember you also supposed $a-b=1$, which would need to be true at the same time. $\endgroup$
    – aschepler
    May 24 at 11:06

2 Answers 2


Well, you seem to be doing a very good job up until when you realize that

one must have $(a-b)(a^2+ab+b^2)= 2011$.

You then come to the key observation $a-b$ must be a divisor of $2011$.

At this point I would consider the problem "almost solved", it seems like now we must only do some case checking and everything will be fine.

Case $1$: $a-b = 1$. We get $b=a-1$ and so we have $a^2 + (a-1)a + a^2 = 2011$.

Case $2$: $a-b= 2011$. We get $b= a-2011$ and so we must have $(2011)(a^2 + (a-2011)a + (a-2011)^2) = 2011$.

Case $3$: $a-b= -1$. We get $b= a+1$ and so we must have $-(a^2 + (a+1)a + (a+1)^2) = 2011$.

Case $4$: $a-b= -2011$. We get $b= a+2011$ and so we must have $-2011(a^2 + (a+2011)a + (a+2011)^2) = 2011$.

Now, do these cases have solutions? These are the sort of equations that can be "solved" with the quadratic formula ! So you can get the answers needed.


The possible values or $x^3\pmod 9$ are $\{0,1,-1\}$ only.

So their difference can only take the values $\{0,1,2,-1,-2\}$, yet $2011\equiv 4\pmod 9$ so it is not reachable.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.